Augmenting Exposure Therapy: Mobile Augmented Reality for Specific Phobia - De Witte, Nele A. J.; Scheveneels, Sara; Sels, Romy; Debard, Glen; Hermans, Dirk; Van Daele, Tom (Frontiers in Virtual Reality, 2020)
New technologies, such as virtual reality (VR) and augmented reality (AR), can be used as an add-on to exposure therapy for common anxiety disorders. While the benefits of VR for exposure therapy have already been demonstrated extensively in research, AR applications are only just becoming widely available. Evidence for the added value and effectiveness of augmented reality exposure therapy (ARET) is still scarce. The current study aimed to explore whether a first markerless AR iOS app for specific phobia could induce fear for multiple animal species in a general population sample. In two experiments participants made use of the Phobos AR app in a behavioral approach task (BAT), using animals for which they were anxious, but not phobic. Self-report data and physiological measures were recorded. In Experiment 1, 108 participants chose one of the seven available animal species and were either allocated to a smartphone or tablet condition. Results showed increasing levels of self-reported anxiety with increasing levels of BAT difficulty. However, this increase was smaller in individuals reporting low levels of perceived realism. No effects on heart rate (HR) could be established. In Experiment 2, 52 participants were exposed to virtual spiders. For both self-reported anxiety and the interaction with perceived realism, results were similar to Experiment 1. Skin conductance did increase significantly from baseline to the highest level of difficulty of the BAT and the severity of fear of spiders also appeared to be related to the fear response in the BAT. In conclusion, the study shows that animals presented in AR through a mobile device can evoke anxiety, which is a prerequisite for the implementation of ARET. However, further research should establish the effects of ARET in a clinical sample of people with specific phobias.